Covalent Inhibition of the Lymphoid Tyrosine Phosphatase. Issue 2 (8th January 2014) - Ahmed, Vanessa F.; Bottini, Nunzio; Barrios, Amy M.
Abstract Covalent inhibitors of lymphoid tyrosine phosphatase (LYP) were identified from a screen of the NIH Molecular Libraries Small Molecules Repository (MLSMR). Both of the two lead compounds identified have phosphotyrosine‐mimetic benzoic acid moieties as well as electrophilic acrylonitrile groups. Inhibition kinetics of both compounds are consistent with covalent modification of the enzyme, with nanomolar KI and reciprocal millisecond kinact values, representing the best efficiency ratios (kinact/KI) among currently reported covalent LYP inhibitors. Covalent inhibitors can provide longer efficacy and better selectivity than more conventional noncovalent inhibitors, and these lead compounds are an important step toward the development of protein tyrosine phosphatase (PTP)‐targeted covalent therapeutic compounds.